Hydrolysis of Mixed Sugarcane Bagasse and Rice Husk Using Cellulase Enzyme for Reducing Sugar Production - Pratami, Melyta Rizky; Darmayanti, Rizki Fitria; Nuraini, Nanda Febia; Munawaroh, Faizzatul (Journal of Biobased Chemicals, 2022)
Reducing sugar can be produced from lignocellulosic raw materials. The content of polysaccharides such as cellulose, hemicellulose, and starch will be broken down into simpler carbohydrates. This study used a mixture of sugarcane bagasse and rice husks as lignocellulosic raw materials. The lignin content in the raw material must be removed through delignification or pretreatment so that enzymes can access cellulose and hemicellulose. This study used a physics-chemical pretreatment method, in which lignocellulosic material soak in 3% NaOH then heated with microwave and boiling water. The next process is enzymatic hydrolysis with variations of cellulase enzymes activity 0.434, 0.871, 2.61, and 3.49 FPU/g mixture of bagasse and rice husks. The cellulase enzyme used in this study was also derived from the fungus Trichoderma viride. Analysis of the sugar concentration resulting from hydrolysis used the DNS method with the 3.5-dinitrosalicylic acid reagent. The concentration of sugar from hydrolysis using a variety of enzymes with microwave heating pretreatment and boiling water pretreatment obtained the highest results which were the same at the addition of enzyme activity 3.49 FPU/g substrate at 24 hours, namely 4.077 g/L and 15.18 g/L. The optimum time for enzymatic hydrolysis is 12 hours and optimum enzyme activity is the addition of enzyme activity 2.61 FPU/g. The average concentration of sugar hydrolyzed by the addition of Trichoderma viride solution in pretreatment using microwave heating was 0.7611 g/L with a yield of 21.01 mg sugar/g substrate and with pretreatment in boiling water obtained 0.8679 g/L with a yield of 23.95 mg sugar/g substrate.